Arrow-shaped elasto-inertial rotating waves. - López-Alonso, José Manuel; Altmeyer, Sebastian (The Royal Society, 2023)
We present direct numerical simulations of the Taylor– Couette flow of a dilute polymer solution when only the inner cylinder rotates and the curvature of the system is moderate (η = 0.77). The finitely extensible nonlinear elastic-Peterlin (FENE-P) closure is used to model the polymer dynamics. The simulations have revealed the existence of a novel elastoinertial rotating wave characterized by arrow-shaped structures of the polymer stretch field aligned with the streamwise direction. This rotating wave pattern is comprehensively characterized, including an analysis of its dependence on the dimensionless Reynolds and Weissenberg numbers. Other flow states having arrow-shaped structures coexisting with other types of structures have also been identified for the first time in this study and are briefly discussed.
Keywords: Dinámica de fluidos; Viscoelasticidad; Taylor-Couette flow; Viscoelastic fluid; Rotating waves; Bifurcations; Instability